Faktor-faktor yang mempengaruhi profitabilitas perusahaan non keuangan - ADETYA ALVERINA; MEIRYANANDA PERMANASARI (Jurnal Bisnis dan Akuntansi, 2016)
The purpose of this research is to obtain empirical evidence factors that affect profitability among non-financial companies in Indonesia. The factors are current liability, noncurrent liability, firm size, sales growth, industry, total asset turnover, debt to equity ratio, and current ratio. Population of this research are non financial companies listed in Indonesia Stock Exchange (IDX) over five years period 2009 until 2013. Purposive sampling method used to take the samples. Total non-financial companies which include to this research are 128 companies. Multiple regression analysis is used to test the hypothesis. The research result show that current liability ratio, firm size, industry, total asset turnover, and debt to equity ratio have effect to profitability. While noncurrent liability ratio, sales growth, and current ratio.have no effect to profitability.